2019
DOI: 10.1002/lt.25492
|View full text |Cite
|
Sign up to set email alerts
|

The Intention‐to‐Treat Effect of Bridging Treatments in the Setting of Milan Criteria–In Patients Waiting for Liver Transplantation

Abstract: In patients with hepatocellular carcinoma (HCC) meeting the Milan criteria (MC), the benefit of locoregional therapies (LRTs) in the context of liver transplantation (LT) is still debated. Initial biases in the selection between treated and untreated patients have yielded conflicting reported results. The study aimed to identify, using a competing risk analysis, risk factors for HCC‐dependent LT failure, defined as pretransplant tumor‐related delisting or posttransplant recurrence. The study was registered at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
0
24
0
7
Order By: Relevance
“…LRT prevents wait‐list drop‐off because of tumour progression. In a propensity matched analysis from the UK, one session of LRT was associated with a 49% lower risk of delisting for progression of HCC and/or post‐LT recurrence . This advantage was lost if more than 3 LRTs were needed, which might suggest that poorer tumour biology and/or longer waiting times are risks of a worse outcome.…”
Section: Management Of Patients With Hcc On the Waiting Listmentioning
confidence: 99%
See 1 more Smart Citation
“…LRT prevents wait‐list drop‐off because of tumour progression. In a propensity matched analysis from the UK, one session of LRT was associated with a 49% lower risk of delisting for progression of HCC and/or post‐LT recurrence . This advantage was lost if more than 3 LRTs were needed, which might suggest that poorer tumour biology and/or longer waiting times are risks of a worse outcome.…”
Section: Management Of Patients With Hcc On the Waiting Listmentioning
confidence: 99%
“…In a propensity matched analysis from the UK, one session of LRT was associated with a 49% lower risk of delisting for progression of HCC and/or post-LT recurrence. 8 This advantage was lost if more than 3 LRTs were needed, which might suggest that poorer tumour biology and/or longer waiting times are risks of a worse outcome. The goal of these bridging therapies is to achieve a complete response, defined by the absence of viable tumour on cross-sectional imaging and AFP <100 ng/mL.…”
Section: Manag Ement Of Patients With H CC On the Waiting Lis Tmentioning
confidence: 99%
“…Это и этические причины, и разнородность пациентов с ГЦК, и необходимость анализировать всех рандомизированных пациентов ("intention-to-treat"), которые могут сталкиваться с противопоказаниями к ТП, и т.п. [12]. В связи с этим онкологическая целесообразность ТП при ГЦК реципиентам, не отвечающим Миланским критериям и UCSF, остается неясной.…”
Section: Discussionunclassified
“…Keywords: liver, hepatocellular carcinoma, locoregional therapy, liver transplantation. применение ЛРТ перед ТП даже у пациентов, соответствующих Миланским критериям, улучшает выживаемость после ТП [11][12][13].…”
Section: вве де ниеunclassified
“…Lai et al have shown that patients with progressive disease despite LRT had a higher risk of dropout or posttransplant HCC recurrence (subdistribution HR 5.62, 95% CI 4.10-7.69). 31 Additionally, Mehta et al demonstrated significantly improved post-LT outcomes when restricting LT to patients with a reduction in AFP from >1,000 to <500 ng/ml after LRT. 32 In the near future, the assessment of tumour response on pre-LT imaging can be improved with artificial intelligence methods (e.g.…”
Section: Key Pointsmentioning
confidence: 99%